Mathematical and physical papers. Volume 4 - Stokes, George Gabriel, 1819-1903 (Cambridge : Cambridge University Press, 2009)
Sir George Stokes (1819-1903) established the science of hydrodynamics with his law of viscosity describing the velocity of a small sphere through a viscous fluid. He published no books, but was a prolific lecturer and writer of papers for the Royal Society, the British Association for the Advancement of Science, the Victoria Institute and other mathematical and scientific institutions. These collected papers (issued between 1880 and 1905) are therefore the only readily available record of the work of an outstanding and influential mathematician, who was Lucasian Professor of Mathematics in Cambridge for over fifty years, Master of Pembroke College, President of the Royal Society (1885-1890), Associate Secretary of the Royal Commission on the University of Cambridge and a Member of Parliament for the University.
Originally published in Cambridge at the University Press in 1904.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Physics; Hydrodynamics; Physical optics; Mathematics -- Problems, exercises, etc